A case of primary extragenital cutaneous gonorrhea involving the finger. Issue 4 (October 2021) - Schwerdt, Mary K.; Butala, Sudhir; Hinds, Elaine; Schron, Deborah; Berry, Gregory J.
Abstract : N/A: A case of primary extragenital cutaneous gonorrhea affecting the left middle finger of a 16-year-old female patient is presented. The patient denied a history of sexual activity and the only reported symptoms were finger pain and associated lymphangitis. Wound culture was obtained from an incision, and drainage procedure was performed at an emergency room of a community hospital. Laboratory diagnosis was made at a clinical microbiology laboratory using Gram stain, agar culture, and matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS). Concurrent blood cultures had no growth at 5 days. The patient was switched from Cephalexin and Trimethoprim-sulfamethoaxole to an appropriate regimen upon sensitivity testing. The patient was lost to follow-up, and it is unknown if the possibility of seeding mucosal infection, such as the pharynx, was investigated.